Unveiling the Dynamics of Blended Learning: The Interplay Between Lecturer Competencies and Students' Digital Experience on Student Subjectivity - Siti Suprihatin; Bambang Sugeng; Sugeng Hadi Utomo; Agus Hermawan (STAI Hubbulwathan Duri, 2024)
This research aims to empirically examine the influence of lecturer competencies, students' digital experience, and self-regulated learning moderated by digital learning facilities on students' subjective perceptions of blended learning. The study employs an explanatory quantitative method involving a population of 328 students, with 273 respondents participating in lectures using the blended learning model at universities in Lampung Province. An analysis is conducted using the Moderated Regression Analysis (MRA) model, preceded by tests for normality and reliability. Simultaneous testing of students' subjective perceptions of blended learning indicates a significant value. Another finding in this research reveals that students' experiences, such as knowledge, usage, awareness, information-seeking skills, and information sharing, predominantly influence students' subjective views on blended learning, with a coefficient value approaching one, namely 0.975. Recommendations for future research could focus on evaluating the success of the blended learning model through a combination of face-to-face learning within the classroom and the utilization of Learning Management Systems (LMS), considering the social, cognitive, and affective environment that supports students.